1996
DOI: 10.1029/96gl01410
|View full text |Cite
|
Sign up to set email alerts
|

Seismic and electrical anisotropies in the lithosphere across the Grenville Front, Canada

Abstract: The Grenville Front is a prominent tectonic feature of the Canadian Shield which has been the focus of a LITHOPROBE transect. A strong electrical anisotropy has been detected in a frequency range of 0.1–0.01 Hz (≈ 50 to 150 km), the most conductive direction being oriented N80E. In order to compare electrical and seismic anisotropies, ten seismometers have been deployed across the Grenville Front to record teleseismic events. S‐wave splitting measurements show an average delay of 1.54±0.21 s between the fast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…The direction of maximum conductivity is generally east-west and parallel to the lineations defined by the major deformation zones that have affected the area during Precambrian time. Along the corridor traversed by the teleseismic arrays, the electrical anisotropy shows a fairly uniform orientation of N80°E (Kellett et al 1994;Sénéchal et al 1996). These results are presented in Fig.…”
Section: Geophysical Coveragesupporting
confidence: 62%
See 1 more Smart Citation
“…The direction of maximum conductivity is generally east-west and parallel to the lineations defined by the major deformation zones that have affected the area during Precambrian time. Along the corridor traversed by the teleseismic arrays, the electrical anisotropy shows a fairly uniform orientation of N80°E (Kellett et al 1994;Sénéchal et al 1996). These results are presented in Fig.…”
Section: Geophysical Coveragesupporting
confidence: 62%
“…This paper presents a review of the teleseismic studies that have been performed along the Abitibi-Grenville transect, where two separate arrays were deployed (one in 1994 and the other in 1996). Data from the former array were used for shear-wave splitting analysis and published in Sénéchal et al (1996) and Ji et al (1996); a review of their results and interpretations is presented here. Other studies, involving receiver function analysis and traveltime inversion and shear-wave splitting on the 1996 dataset, are still in progress.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical anisotropy measurements in the Canadian shield (Sénéchal et al, 1996) and the eastern US (Wannamaker et al, 1996) show a very good agreement between the directions of conductivity anisotropy in the upper mantle and the crustal tectonic fabric, suggesting that the mantle and the crustal fabrics are similar.…”
Section: Rheology Of the Lithospherementioning
confidence: 82%
“…Although few measurements are available, they display an internally consistent anisotropy pattern, and a good correlation with shear wave splitting and surface geology. Sénéchal et al (1996), for instance, through coupled shear wave splitting measurements and magnetotelluric soundings along a transect in the Canadian shield, retrieved similar directions of anisotropy from both datasets and, considering that the measured electrical anisotropy originates between 50 and 150 km, they concluded that the seismic anisotropy also originates from a well-defined fabric in the lithospheric upper mantle fabric. Similar preliminary results have been obtained in the Appalachians (Wannamaker et al, 1996) and the Pyrenees (Pous et al, 1995;M.…”
Section: Tectonic Fabric Of the Continental Lithospheric Mantlementioning
confidence: 99%
See 1 more Smart Citation